Pengaruh Promosi, Kualitas Layanan dan Branding Terhadap Loyalitas Pelanggan Menggunakan Dompet Digital Shopeepay sebagai Metode dan Teknik Pembayaran - Melva Hermayanty Saragih; Andrew Danielle Prayitta (Universitas Nusantara PGRI Kediri, 2023)
This study aims to determine the effect of Promotion, Service Quality, and Branding on customer loyalty using the ShopeePay digital wallet as a payment method and technique. The study used quantitative methods sourced from respondents' questionnaires as the primary source of research. The research population is the ShopeePay digital wallet users in Jakarta and the sample is 106 people as respondents. Through simple regression, the result is that there is a significant effect of the Promotion, Service Quality and Branding variables on the Customer Loyalty variable. Meanwhile, through multiple regression, the result is that there is no significant effect between Promotion and Service Quality on Customer Loyalty, but there is a significant effect between Branding on Customer Loyalty.